HUBUNGAN INTENSITAS KEBIASAAN BERMAIN GAME ONLINE TERHADAP HASIL BELAJAR SISWA KELAS V SDN GUGUS V MATARAM TAHUN AJARAN 2019/2020 - Sulistiyoningsih, Dirgantari; Darmiany, Darmiany; Istiningsih, Siti (Jurnal Ilmiah Pendidikan Indonesia, 2021)
This study aims to determine whether there is a relationship of intensity of playing online game with learning results of mathematic students 5 in class of primary school group 05sub districk of Mataram. Learning outcomes are focused on Matematika. The method used in this research is descriptive correlational. The population in this study was 199 spread from six school. It used probability simple random sampling with a sample as many as 66 students. The collection of data used questionnaire and documentation methods. The data analysis method used to test hypothesis is product moment correlation. The results of this study showed that there no correlation between the intensity of playing online game with learning results of mathematic rcount 0,161 while rtable N = 66 at the 10% significance level is 0,2423, so rcount < rtable (0,161 < 0,2423) wich can be interprate Ha was rejected and Ho was accepted. Based explanation above, it can,t be conclude that there are correlation or relation beetwen intensity of playing online game habits with learning results of mathematics students V in class of primary school group V sub districk of Mataram in academic year of 2019/2020.